Multicentric Case-Control Study on Azathioprine Dose and Pharmacokinetics in Early-onset Pediatric Inflammatory Bowel Disease. - Stocco, Gabriele; Martelossi, Stefano; Arrigo, Serena; Barabino, Arrigo; Aloi, Marina; Martinelli, Massimo; Miele, Erasmo; Knafelz, Daniela; Romano, Claudio; Naviglio, Samuele; Favretto, Diego; Cuzzoni, Eva; et al. (Inflamm Bowel Dis, 2017)
BACKGROUND: Early-onset inflammatory bowel disease (IBD) is generally aggressive, with a high probability of complications and need of surgery. Despite the introduction of highly effective biological drugs, treatment with azathioprine continues to be important even for early-onset IBD; however, in these patients azathioprine response seems to be reduced. This study evaluated azathioprine doses, metabolite concentrations, and their associations with patients' age in children with IBD treated at 6 tertiary pediatric referral centers. METHODS: Azathioprine doses, metabolites, and clinical effects were assessed after at least 3 months of therapy in 17 early-onset (age < 6 yr, cases) and 51 nonearly-onset (aged > 12 and <18 yrs, controls) patients with IBD. Azathioprine dose was titrated on therapeutic efficacy (response and adverse effects). Azathioprine metabolites and thiopurine methyltransferase activity were determined by high-performance liquid chromatography with ultra violet-vis detection (HPLC-UV) methods. RESULTS: Frequency of patients in remission was similar among early-onset and control groups, respectively (82% and 84%, P value = 0.72). Early-onset patients required higher doses of azathioprine (median 2.7 versus 2.0 mg·kg·d, P value = 1.1 × 10). Different doses resulted in comparable azathioprine active thioguanine nucleotide metabolite concentrations (median 263 versus 366 pmol/8 × 10 erythrocytes, P value = 0.41) and methylmercaptopurine nucleotide concentrations (median 1455 versus 1532 pmol/8 × 10 erythrocytes, P value = 0.60). Lower ratios between thioguanine nucleotide metabolites and azathioprine doses were found in early-onset patients (median 98 versus 184 pmol/8 × 10 erythrocytes·mg·kg·d, P value = 0.017). Interestingly, early-onset patients presented also higher thiopurine methyltransferase activity (median 476 versus 350 nmol methylmercaptopurine/mg hemoglobin/h, P-value = 0.046). CONCLUSIONS: This study demonstrated that patients with early-onset IBD present increased inactivating azathioprine metabolism, likely because of elevated activity of the enzyme thiopurine methyltransferase.
Keywords: Adolescent; Age of Onset; Antimetabolites; Azathioprine; Case-Control Studies; Child; Child, Preschool; Chromatography, High Pressure Liquid; Dose-Response Relationship, Drug; Erythrocytes; Female; Guanine Nucleotides; Humans; Inflammatory Bowel Diseases; Male; Mercaptopurine; Methyltransferases; Thioguanine